Reducing WAD Cyanide At The Discharge Spigot (dda097cf-c258-4703-898a-7d09300cbbc0) (The Southern African Institute of Mining and Metallurgy, 2007)
In a gold CIP/CIL circuit, adding new circuit water to a final tails thickener and then directing the thickener overflow to the head of the circuit significantly reduces the cyanide concentration at the TSF discharge spigot. The new water is used to dilute the final tails. The dilution and recycle of the tails in this manner may have the added benefit of reducing reagent consumption, in some cases to the point where the reagent savings justify the expenditure and Cyanide Code compliance is achieved at no extra cost. Potential circuit configurations and water recycles can be modelled by splicing a flowsheeting and thermodynamics package, such that changes to the composition of the water can be reduced to chemical speciation with a Gibbs free energy minimisation enabling a complete understanding of the circuit water chemistry.